Converts of Village and Self-identity Construction of The Converted Community in Lembang Subdistrict Pinrang Regency - Aswar Tahir (LPPM IAIN Parepare, 2021)
Converts of Village is a place to live for the families of converts in lembang subdistrict Pinrang, in addition it is also a special environment for converts to learn the values of Islamic diversity teachings. This study aims to analyze how the converted of village as a special environment can reconstruct the identity of the converted community. This artike uses qualitative methods, data collection techniques are conducted with in-depth interviews, direct observations and documentation, while data analysis techniques through data reduction, data presentation and data verifakasi or conclusion drawing. The results showed that the converted village is an environment that can reconstruct the identity of the converted community to become Muslim religious. The view of the converts towards themselves related to their identias is to consider themselves as religious Muslims who perform worship in accordance with Islamic law. Meanwhile, the view of non-Muslim people around the converted village is to accept the existence of the convert community because the converts still have family ties with non-Muslim people in the region.